Analisis Penggunaan Aplikasi Evaluasi Belajar Online Pada Pembelajaran Biologi di SMA Kota Jambi: (Analysis of the Use of Online Learning Evaluation Applications in Biology Learning in Jambi City High Schools) - Odian Tambunan; Risnita Risnita; Bambang Hariyadi (BIODIK, 2023)
One of the measuring tools for evaluating learning outcomes is using a test. As information technology develops, written tests using paper media have changed to online-based tests. This research is quantitative descriptive. The data source for this research was obtained directly from teachers and students using interviews, survey questionnaires, and documentation results. The results of the study show that the online test applications used in Biology lessons at Jambi City Public High Schools are Google Forms, Google Classroom, Edmodo and e-exam applications. The online exam application is used during daily tests, midterm exams and final semester exams. The advantages of the online exam application used are that it does not use paper, fast, saves money, effort and time, exam results can be known quickly. Then the weakness is having to use a stable internet network, requiring internet quota and it is difficult to prevent students from cheating when exams are carried out at home. The obstacle felt by the teacher is that the exam questions must be typed one by one in the application, not all students have an Android smartphone, if the device has too many applications it will take a long time to open the exam application. And the network often lags. The effectiveness of implementing online exam applications is effective in technical terms such as speed of processing time, effort and cost. However, online exam applications are less effective in terms of increasing student learning outcomes and honesty. In general, the responses of teachers and students showed a positive response, respectively 70.52% and 65.78% with good criteria. Abstrak. Salah satu alat ukur evaluasi hasil belajar adalah menggunakan tes. Seiring berkembangnya teknologi informasi, tes terlulis dengan media kertas, berubah menjadi tes berbasis online. Penelitian ini merupakan penelitian deskriptif kuantitatif. Sumber data penelitian ini diperoleh langsung dari guru dan siswa dengan menggunakan wawancara, angket survei, dan hasil dokumentasi. Hasil penelitian menunjukkan aplikasi ujian online yang digunakan dalam pembelajaran Biologi di SMA Negeri Kota Jambi adalah Google Form, Google Classroom, Edmodo dan Aplikasi e-ujian. Aplikasi ujian online digunakan pada saat ulangan harian, ujian tengah semester dan ujian akhir semester. Kelebihan dari aplikasi ujian online yang digunakan adalah tidak menggunakan kertas, cepat, hemat biaya, tenaga dan waktu, hasil ujian dapat diketahui dengan cepat. Kemudian kelemahanya adalah harus menggunakan jaringan internet yang stabil, memerlukan kuota internet dan sulit menghindari siswa untuk berbuat curang ketika ujian dilaksanakan dirumah. Kendala yang dirasakan guru adalah soal ujian harus diketik satu persatu di aplikasi, tidak semua siswa memiliki smartphone android, apabila perangkat terlalu banyak aplikasi maka akan membutuhkan waktu yang lama untuk membuka aplikasi ujian. Serta jaringan sering ngelag. Efektivitas penerapan aplikasi ujian online efektif dalam hal teknis seperti kecepatan waktu pengerjaan, tenaga dan biaya. Namun, aplikasiÂ  ujian online kurang efektif dalam hal peningkatan hasil belajar dan kejujuran siswa. Secara umum respon guru dan siswa menunjukkan respon yang positif masing-masing persentase 70,52% dan 65,78% dengan kriteria baik. Kata kunci: Aplikasi, Kota Jambi, Online, Ujian.